The role of the forward capacity market in promoting electricity use reduction - Liu, Y (2017)
Electricity use reduction is at the heart of an energy policy landscape increasingly defined by climate change, security and affordability. With its potential of peak demand reduction, it can be used as a cost-effective alternative to generation for contributing to capacity adequacy. In many restructured electricity markets, the forward capacity market is established as a solution to ensure capacity adequacy, with some of them allowing electricity use reduction to compete against other resources. To promote electricity use reduction, financial incentives for investment in end-use electric energy efficiency (EE) are crucial. This thesis focuses on one novel approach of relying on the forward capacity market to incentivise electric efficiency investment, which is trialled in the Electricity Demand Reduction (EDR) Pilot in the UK. It aims to examine the role of the forward capacity market in promoting electricity use reduction, by asking two broad research questions: 1) whether the forward capacity market can serve as a primary policy vehicle to give financial incentives to support electricity use reduction; and 2) whether, as one mechanism for ensuring capacity adequacy, it can promote electricity use reduction as a capacity resource. Case studies are conducted of the EDR Pilot, the Great Britain Capacity Market, ISO New England (ISO-NE), PJM and international electric efficiency schemes. They demonstrate that the forward capacity market, with its focus on peak savings and a savings-based approach for providing financial incentives, only plays a minor role in advancing the objective of incentivising investment in electric EE measures. The general design features of the forward capacity market pose higher requirements of participation, which may create barriers for some key customer segments to access financial incentives or target specific efficiency measure. The capacity payment, under the current market structure, may only provide a lukewarm incentive for customers to strengthen their capabilities to access support from the forward capacity market. However, it is valuable to integrate electricity use reduction in the forward capacity market. It is a viable mechanism to reward the capacity value of electricity use reduction, which requires the appropriate definition of capacity product, regulatory support for electricity use reduction and the removal of participation barriers.